Aplikasi Katalog Penjualan Produk Makanan Kucing Dengan Mengimplementasikan Augmented Reality Berbasis Android - Dorlika Safitra Harefa; Haida Dafitri; Sumi Khairani (Jurnal Ilmu Komputer dan Sistem Informasi, 2024)
Cats are popular pets, but choosing the right food for them can be a challenge. Conventional cat food product sales catalogs may no longer be attractive enough for modern consumers who are used to advanced technology. Therefore, this study proposes the implementation of Augmented Reality (AR) in an Android-based cat food product sales catalog application. By using AR, consumers can see cat food products in real life and listen to product descriptions in voice form. The results of this study stated that 21 respondents strongly agreed with this application, with an approval rate of about 80%. This shows that the application is very useful in helping cat owners choose the appropriate food.